2002
DOI: 10.1892/0891-6640(2002)016<0080:eoefpo>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Enalapril for Prevention of Congestive Heart Failure in Dogs with Myxomatous Valve Disease and Asymptomatic Mitral Regurgitation

Abstract: We evaluated the long-term effect of early angiotensin-converting enzyme (ACE) inhibition (enalapril maleate) as monotherapy to postpone or prevent congestive heart failure (CHF) in asymptomatic dogs with mitral regurgitation (MR) attributable to myxomatous valvular disease (MVD) in a prospective, randomized, double-blinded, placebo-controlled multicenter trial involving 14 centers in Scandinavia. Two hundred twenty-nine Cavalier King Charles (CKC) Spaniels with MR attributable to MVD but no signs of CHF were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
166
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(185 citation statements)
references
References 16 publications
12
166
1
6
Order By: Relevance
“…Several studies have reported efficacy of ACEI drugs in the management of dogs with heart disease associated with MMVD. Two clinical trials designed to determine whether treatment with enalapril would prevent or delay onset of CHF in small breed dogs with MMVD reported limited12 benefit or lack of clinical effect 13. Benazepril used alone or as an add‐on to standard treatment in MMVD or DCM dogs with CHF extended life span compared to dogs that did not receive benazepril 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported efficacy of ACEI drugs in the management of dogs with heart disease associated with MMVD. Two clinical trials designed to determine whether treatment with enalapril would prevent or delay onset of CHF in small breed dogs with MMVD reported limited12 benefit or lack of clinical effect 13. Benazepril used alone or as an add‐on to standard treatment in MMVD or DCM dogs with CHF extended life span compared to dogs that did not receive benazepril 34.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial data are limited in dogs, and the majority of studies have focused on treatment to manage chronic myxomatous valvular disease (MMVD). Trials using enalapril and conducted largely in populations of dogs with advanced heart disease but not heart failure have reported limited benefit or no benefit in these populations 12, 13. Digitalis traditionally has been used to manage supraventricular tachyarrhythmias14 and dilated cardiomyopathy in dogs,14, 15, 16 but evidence for clinical efficacy is sparse.…”
mentioning
confidence: 99%
“…In the remaining 39 dogs, MR attributable to chronic mitral valve disease was identified by the same examinations. The dogs with MR were divided into 4 categories-Group I (n=12), Group II (n=12), Group III (n=9), and Group IV (n=6) based on the modified New York Heart Association functional classification for heart failure (NYHA class) [21]. In addition, Groups I and II were categorized as compensated congestive heart failure (CHF) [CHF (-), n=24], and Groups III and IV were categorized as decompensated CHF [CHF (+), n=15].…”
Section: Validation Of Correlation Of LV Function Between Pulsed Tdi mentioning
confidence: 99%
“…Because AVD is characterized by chronic progression, to date, there is little an owner or veterinarian can do to alter the disease process. Evidence suggests that benazepril might be beneficial in dogs with asymptomatic heart disease,22 but 2 trials23, 24 were not able to demonstrate a significant effect of enalapril on time to develop CHF. DCM is characterized by a slowly progressive presymptomatic phase during which ventricular premature contractions occur along with progressive left ventricular dysfunction and, usually, progressively more severe ventricular tachyarrhythmias 25, 26, 27.…”
mentioning
confidence: 99%